2018
DOI: 10.1016/s0140-6736(18)30206-x
|View full text |Cite|
|
Sign up to set email alerts
|

Extrafine inhaled triple therapy versus dual bronchodilator therapy in chronic obstructive pulmonary disease (TRIBUTE): a double-blind, parallel group, randomised controlled trial

Abstract: Chiesi Farmaceutici.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
474
1
53

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(556 citation statements)
references
References 22 publications
28
474
1
53
Order By: Relevance
“…A comprehensive electronic database search provided 1,139 studies for review, and manual search identified 39 additional studies. After review, 12 RCTs comparing triple inhaler therapy with dual inhaler therapy in patients with moderate‐to‐severe COPD remained and were included in the analysis . We have excluded trials that evaluated the de‐escalation of triple therapy to dual therapy as patients in both treatment arms received triple inhaler before de‐escalation to dual therapy which could affect the results .…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive electronic database search provided 1,139 studies for review, and manual search identified 39 additional studies. After review, 12 RCTs comparing triple inhaler therapy with dual inhaler therapy in patients with moderate‐to‐severe COPD remained and were included in the analysis . We have excluded trials that evaluated the de‐escalation of triple therapy to dual therapy as patients in both treatment arms received triple inhaler before de‐escalation to dual therapy which could affect the results .…”
Section: Resultsmentioning
confidence: 99%
“…In der randomisierten Doppelblindstudie TRIBUTE wurde die Wirksamkeit der extra feinen Dreifach-Fixkombination (GB/ FF/ BDP) mit der LAMA/LABA-Kombination aus GB/Indacaterol (IND) hinsichtlich der Reduktion moderater bis schwerer Exazerbationen bei COPD verglichen [1]. Bei vergleichbarem Sicherheitsprofil erreichte GB/FF/BDP den primären Studienendpunkt mit einer signifikanten Reduktion der Rate moderater bis schwerer Exazerbationen um 15,2% im Vergleich zu GB/IND (p = 0,043) [1].…”
Section: Tribute -Extrafeine Dreifach-fixkombination üBerlegenunclassified
“…Bei vergleichbarem Sicherheitsprofil erreichte GB/FF/BDP den primären Studienendpunkt mit einer signifikanten Reduktion der Rate moderater bis schwerer Exazerbationen um 15,2% im Vergleich zu GB/IND (p = 0,043) [1]. Eine Überlegenheit zeigte sich auch in der Subgruppe der GOLD-B-Patienten: Hier konnte die Dreifachtherapie moderate bis schwere Exazerbationen um 23% reduzieren [8].…”
Section: Tribute -Extrafeine Dreifach-fixkombination üBerlegenunclassified
“…The incidence of pneumonia was, however, significantly increased in patients receiving an ICS [70]. Therefore, triple therapy should be considered in selected, symptomatic patients with severe airflow obstruction and at least one exacerbation in the previous year [71].…”
Section: Triple Inhaled Therapymentioning
confidence: 99%